Herpes Simplex Virus Type 2 Immediate Early Protein ICP27 Inhibits IFN-β Production in Mucosal Epithelial Cells by Antagonizing IRF3 Activation - Guan, Xinmeng; Zhang, Mudan; Fu, Ming; Luo, Sukun; Hu, Qinxue (Frontiers in Immunology, 2019)
Herpes simplex virus type 2 (HSV-2) is the main cause of genital herpes and its infection is common in the lower genital tract. Although neuronal and immune cells can be infected, epithelial cells and keratinocytes are the primary HSV-2 target cells. HSV-2 establishes latency by evading the host immune system and its infection can also increase the risk of HIV-1 sexual transmission. Our pervious study found that HSV-2 immediate early protein ICP22 inhibited IFN-β production by interfering with the IRF3 pathway. However, ICP22-null HSV-2 did not completely loss the capability in suppressing IFN-β induction, suggesting the involvement of other viral components in the process. In this study, by using an ex vivo cervical explant model, we first demonstrated that HSV-2 can indeed inhibit IFN-β induction in human mucosal tissues. We further identified HSV-2 immediate early protein ICP27 as a potent IFN-β antagonist. ICP27 significantly suppresses Sendai virus or polyinosinic-polycytidylic acid-induced IFN-β production in human mucosal epithelial cells, showing that ICP27 inhibits IFN-β promoter activation and IFN-β production at both mRNA and protein levels. Additional studies revealed that ICP27 directly associates with IRF3 and inhibits its phosphorylation and nuclear translocation, resulting in the inhibition of IFN-β induction. Our findings provide insights into the molecular mechanism underlying HSV-2 mucosal immune evasion and information for the design of HSV-2 mucosal vaccines.